Determining Agricultural Premium Insurance in Malang City using Black Scholes Model - Widi, Herlia; Lani, Dea Nisa Rahma; Hasanah, Faridatul (International Journal of Global Operations Research, 2021)
This study examines the determination of rainfall-based agricultural insurance premium prices using the Black-Scholes model. The Black-Scholes model was originally used to determine the price of European-type options. The research method used is a literature study with secondary data collection. The data used in this study are rainfall data and rice production results in the city of Malang from 2015 to 2020. Based on the results and discussion, rainfall which is strongly correlated with rice production results is in quarter 2. The premium results obtained are different according to the desired percentile. In addition to percentiles, taking R_0 also affects the premium price. When R_0=322, the premium price tends to be cheaper than R_0=271.